Enhanced Electrical Conductivity of Graphite through Band Gap Reduction by Ferrite Nanoparticles - Ajay Kumar; Shikha Aeron; Manish Pant; Hari Krishan; Saifullah Zaphar; Ankit Mittal; Narinder Kumar (Zanco Journal of Pure and Applied Sciences)
In this study, an effort was made to fabricate a series of electrically conductive papers (ECPs) by dispersing varying concentrations (%, w/w) of ferrite nanoparticles (FNPs, 8.27 nm) into a graphite matrix bind with hydroxypropyl methylcellulose (HPMC, 46.15%, w/w) and depositing this composite over cellulose paper (CP) (4 cm²). FNP concentrations ranged from 1.0% to 3.0%. The surface characteristics of the ECPs were analyzed using SEM, while XRD was employed to confirm the crystallinity of the coating. The crystallite size of FNPs was calculated from the XRD data using the Scherrer equation. The effect of FNP addition on the thermal stability of the ECPs was also assessed. To confirm the semiconducting nature of ECPs, DC conductivity (σDC) was measured via the four-probe method. Additionally, diffuse reflectance spectroscopy was used to evaluate the effect of coating on the optical band gap (OBG) of the nanocomposities (NCs) over cellulose paper. Notably, FNPs significantly contributed to the reduction of the graphite-coated ECPs' band gap. This study presents a simple, reproducible method for fabricating and characterizing ECPs, highlighting their potential as electrodes for energy conservation and storage applications.